Auto-defense of skin and melanin regulation through glutathione reductase modulation: a new insight - Vadivel, Aruna; Venkata, Amruthavalli Gatla; Rajagopal , Gayathri (International Journal of Research in Dermatology, 2024)
Background: The present study is to understand the Siddha cosmetic preparation - Eve fresh skinbrite cream/herbal extracts used in the cream in down-regulating the melanogenesis process and upregulating glutathione activity to offer skin lightening benefit. Methods: The effect of certain herbal extracts or the combination in reducing tyrosinase activity and associated melanin formation was evaluated in B16F10 melanoma cells and also up regulating glutathione reductase activity leading to the conversion of a reduced form of glutathione (GSH) from GSSG. Results: The extract of Berberis aristata exhibited even activity in inhibiting both tyrosinase and melanin in B16F10 melanoma cell lines. The extract combination also showed a greater effect on increasing GR activity. Conclusions: The herbal ingredients individually and as a combination exhibited strong effects in reducing tyrosinase activity and also upregulating GR activity and thereby reducing skin pigmentation.